Qualitative Analysis Of Determining Factors Of Customer Satisfaction PT. Oso Sekuritas Cab.Galeri MH Thamrin University - Karendita Dayri Prawira; Bambang Purwoko Kusumo Bintoro (Jurnal Scientia, 2024)
This study aims to identify factors influencing customer satisfaction in PT.OSO Securities, MH University gallery branch. Thamrin and describe it based on customer perceptions. This research uses a qualitative approach with case study strategy. Data collection techniques used are interviews, observation, and document review. The participants of this study were 25 customers with different backgrounds (students or employees). The results of the study show that factors influencing customer satisfaction in PT.OSO Securities, MH University gallery branch. Thamrin Branch is the excellent relationship between the employee and the costume, accuracy in satisfying customer desires or demand and adequate facilities in the investment gallery. This strategy will always be improved by the employees to provide customer satisfaction in the long term